Mediation of the APOE Associations With Cognition Through Cerebral Blood Flow: The CIBL Study - Wang, Yan-Li; Sun, Mengfan; Wang, Fang-Ze; Wang, Xiaohong; Jia, Ziyan; Zhang, Yuan; Li, Runzhi; Jiang, Jiwei; Wang, Linlin; Li, Wenyi; Sun, Yongan; Chen, Jinglong; et al. (Frontiers in Aging Neuroscience, 2022)
Background: The ε4 allele of the apolipoprotein E (APOE) gene is a strong genetic risk factor for aging-related cognitive decline. However, the causal connection between ε4 alleles and cognition is not well understood. The objective of the current study is to identify the roles of cerebral blood flow (CBF) in cognitive-related brain areas in mediating the associations of APOE with cognition. Method: The multiple linear regression analyses were conducted in 369 subjects (mean age of 68.8 years; 62.9% female; 29.3% APOE ɛ4 allele carriers). Causal mediation analyses with 5,000 bootstrapped iterations were conducted to explore the mediation effects. Result: APOE ɛ4 allele was negatively associated with cognition (P <0.05) and CBF in amygdala, hippocampus, middle temporal gyrus, posterior cingulate and precuneus (all P <0.05). The effect of the APOE genotype on cognition was partly mediated by the above CBF (all P <0.05). Conclusion: CBF partially mediates the potential links between APOE genotype and cognition. Overall, APOE ɛ4 allele may lead to a dysregulation of the vascular structure and function with reduced cerebral perfusion, which in turn leads to cognitive impairment.